Mapping of the internal structure of human habenula with ex vivo MRI at 7T - Strotmann, Barbara; Kögler, Carsten; Bazin, Pierre-Louis; Weiss, Marcel; Villringer, Arno; Turner, Robert (Frontiers in Human Neuroscience, 2013)
The habenula is a small but important nucleus located next to the third ventricle in front of the pineal body. It helps to control the human reward system and is considered to play a key role in emotion, showing increased activation in major depressive disorders. Its dysfunction may underlie several neurological and psychiatric disorders. It is now possible to visualize the habenula and its anatomical subdivisions -- medial habenula (MHB) and lateral habenula (LHB) -- using MR techniques. The aim of this study is to further differentiate within human lateral habenula (LHB) using ex vivo ultra-high field MR structural imaging, to distinguish between a medial part (m-LHB) and a lateral part (l-LHB). High resolution T1w images with 0.3-mm isotropic resolution and T2*w images with 60-micrometer isotropic resolution were acquired on a 7T MR scanner and quantitative maps of T1 and T2* were calculated. Cluster analysis of image intensity was performed using the Fuzzy and Noise Tolerant Adaptive Segmentation Method (FANTASM) tool. Ultra-high resolution structural MRI of ex-vivo brain tissue at 7T provides sufficient SNR and contrast to discriminate the medial and lateral habenular nuclei. Heterogeneity was observed in the lateral habenula (LHB) nuclei, with clear distinctions between lateral and medial parts (m-LHB, l-LHB) and with the neighbouring medial habenula (MHB). Clustering analysis based on the T1 and T2* maps robustly shows 4 to 6 clusters as subcomponents of lateral and medial habenula.